2018
DOI: 10.1177/2150135117752122
|View full text |Cite
|
Sign up to set email alerts
|

Association of Habitual Activity and Body Mass Index in Survivors of Congenital Heart Surgery: A Study of Children and Adolescents With Tetralogy of Fallot, Transposition of the Great Arteries, and Fontan Palliation

Abstract: Increased habitual activity was associated with lower BMI, emphasizing the potential role of recreational sport in the health of children with congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
20
2
Order By: Relevance
“…36 The time spent in physical activity in our sample of CCHD was 3.59 hours per week, which is lower than 5.9 hours in subjects with Tetralogy of Fallot, transposition of the great arteries, and a Fontan circulation, as reported by O'Byrne et al (2018). 35 In our study, there was no significant association between physical activity and BMI categories, which was found in the O'Byrne et al study 35 . However, we identified an association between a sedentary lifestyle among children and being overweight/obese.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…36 The time spent in physical activity in our sample of CCHD was 3.59 hours per week, which is lower than 5.9 hours in subjects with Tetralogy of Fallot, transposition of the great arteries, and a Fontan circulation, as reported by O'Byrne et al (2018). 35 In our study, there was no significant association between physical activity and BMI categories, which was found in the O'Byrne et al study 35 . However, we identified an association between a sedentary lifestyle among children and being overweight/obese.…”
Section: Discussioncontrasting
confidence: 59%
“…34 However, the findings differ from those of studies that have reported a prevalence of 18.2%-35.7% for overweight/obesity in CCHD in Western countries. [11][12][13][14][15][16][17][18][19]35 This suggests that findings from Western studies cannot be generalized for Asian populations and that studies such as the present one are necessary. Our study also indicated that BMI in the CCHD did not differ significantly from the age-and sex-adjusted BMI of the children in the general Taiwanese population.…”
Section: Discussionmentioning
confidence: 85%
“…Twenty-six of the included studies were cross-sectional studies that examined the prevalence of overweight and obesity in patients with CHD [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and four were cohort studies that investigated the longitudinal change of the prevalence across the lifespan [ 10 , 43 , 44 , 45 ]. The body composition of patients with CHD was compared to a healthy reference cohort in 13 of the included studies [ 20 , 21 , 22 , 23 , 24 , 28 , 29 , 30 , 33 , 35 , 40 , 41 , 45 ], whereas 9 studies merely investigated the prevalence of overweight and obesity in patients with CHD [ 10 , 17 , 18 , 19 , 24 , 32 , 36 ,…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from a group in Philadelphia had reported the positive effect of exercise on BMI in the adolescent population with CHD and found that increasing exercise duration was associated with lower BMI (P = 0.01). 23 The possibility of intervention into a modifiable risk factor before non-emergent cardiothoracic surgery represents a great opportunity to improve outcomes in this population. Further studies should evaluate if intervention in the preoperative period with a structured program aimed to decrease BMI can improve short-term post-operative outcomes in this population.…”
Section: Obesity and Short-term Outcomes In Paediatric Cardiac Criticmentioning
confidence: 99%